MANAJEMEN KEUANGAN DALAM PENDIDIKAN AGAMA ISLAM - Nurul Citra Lestari; Reffy Ananda Rizki; Suprihatin; Dikriyah; Nazwatul Padilah; Nurjamilah; Ilma (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine financial management in Islamic religious education through a library research method, utilizing various relevant sources such as books, journal articles, and previous research findings. A descriptive qualitative analysis was employed to explore the principles and implementation of effective financial management in Islamic educational institutions. The findings indicate that financial management in Islamic education should be based on Islamic values such as trustworthiness, transparency, accountability, justice, efficiency, and effectiveness, which serve as the foundation for a professional, accountable, and worship-oriented financial system. The financial management process includes planning, organizing, budget implementation, as well as supervision and evaluation, all of which aim to ensure the effective and efficient use of funds to improve the quality of education. Applying these principles enables educational institutions to establish sustainable financial governance, strengthen public trust, and support the comprehensive achievement of the vision and mission of Islamic education.